Mechanophore-linked hydroxyl-terminated polybutadiene for the remote detection and quantification of mechanical stress - Kister, Guillaume; Moniruzzaman, Monir; Khan, M.; Debnath, S. (Elsevier, 2018)
Polymers containing chromophores often exhibit mechanoresponsive behaviour, allowing the remote detection of stress in components such as rocket motors without taking the rockets out of service. Here we describe a polymer comprising a difunctional spiropyran chromophore and methyl methacrylate cross-linked with hydroxyl-terminated polybutadiene (HTPB). This polymer was developed as a sensor for the non-destructive monitoring of mechanical stress by using the force-induced colour changes as a quantitative readout. After about 40 N of load was applied there was a gradual colour changes proportional to the compressive forces on the sample, as revealed by in-situ monitoring using a video camera and UV–Vis spectrometry. The tests highlighted a gradual decrease in the transmitted light intensity at 675 nm with increasing load, due to the opening of the spiropyran rings and their conversion to the coloured merocyanine forms. A reversible change to the initial colour occurred 72 h after the load was removed, but only under artificial fluorescent lighting, confirming that visible light is required for the ring-closing reaction. This new polymer is an ideal candidate for the remote detection of stress-induced damage in inaccessible structures or essential equipment that cannot be withdrawn from service for testing.
Keywords: Mechanoresponsive; Detection; Colour-change; Stress; Reversible